Creative Thinking Ability In Mathematics Problem Solving Reviewed by The Personality Type of Senior High School Students In Makassar City - Ahmad Talib (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2021)
This research is a qualitative research with descriptive method. This study aims to describe the ability to think creatively based on the type of student personality, the type of choleric personality in solving mathematical problems. The research subjects were students in the odd semester of class XII IPA 1 SMA Negeri 22 Makassar, the 2019/2020 school year. This subject was chosen by giving a personality questionnaire to students. The data was collected using a mathematical problem solving test instrument on the number sequence material and interviews. The validity of the data was checked by using the triangulation method. The results showed: Students with choleric personality in solving mathematical problems. In question number 1, the subject had difficulty in finding the formula for the nth term. But the subject kept trying and the spirit of trying until finally found the correct formula for the nth term. The subject of the choleric personality type is also said to be able to fulfill the three indicators of creative thinking, namely fluency, flexibility, and novelty. In question number 2, the subject had difficulty finding many ways to solve the problem and only met one indicator of creative thinking, namely fluency.